Computer based real time systems for analyzing cardiovascular response to orthostatic stress - Khan, Munna; Vashisth, Sharda; Vijay, Ritu; Salhan, Ashok K. (Biocybernetics and biomedical engineering, 2015)
The cardiovascular response to orthostatic (gravitational) stress has been the focus of several researches in the past. Average values of hemodynamic variables, such as arterial pressure or heart rate are recorded during changes in posture for diagnosing orthostatic stress clinically. Different methods based on varied physical principles have been developed to measure these hemodynamic variables. Carotid artery is responsible for direction of blood flow to brain and provides a vital physiological parameter which can be used to construe cardiac information. A noninvasive system has been built in which a piezoelectric sensor is positioned on the carotid artery of the subject and carotid signals of fifteen human subjects are acquired in various body postures using application softwares. RR intervals and pulse amplitudes are computed after filtering and analyzing the carotid signal recordings using these softwares. The developed system is validated by determining the percentage change in RR interval and pulse amplitude of all the subjects which is found almost same. The technique used in the proposed system may be applied to measure and manage the orthostatic stress.